2007
DOI: 10.3115/1599600.1599718
|View full text |Cite
|
Sign up to set email alerts
|

Partner modeling is mutual

Abstract: Abstract. Collaborative learning has been hypothesized to be related to the cognitive effort engaged by co-learners to build a shared understanding. The process of constructing this shared understanding requires each team member to build some kind of representation of the behavior, beliefs, knowledge or intentions of other group members. This contribution reports interesting findings regarding to the process of modeling each other. In two empirical studies, we measured the accuracy of the mutual model, i.e. th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Mutual acquaintances possess accurate information about each other (e.g., the work they do, where they live, what they like, and so forth). This information is organized into a mental model that is usually referred to as mutual because of its reciprocal nature [ 21] 3 . Our hypothesis is that this mutual model might help produce more descriptive metadata for the multimedia content because of the implicit knowledge that the peers in a social network might have about the content of a friend.…”
Section: Social Tagging Revamped: Persuasive Techniques and Mutual Momentioning
confidence: 99%
See 2 more Smart Citations
“…Mutual acquaintances possess accurate information about each other (e.g., the work they do, where they live, what they like, and so forth). This information is organized into a mental model that is usually referred to as mutual because of its reciprocal nature [ 21] 3 . Our hypothesis is that this mutual model might help produce more descriptive metadata for the multimedia content because of the implicit knowledge that the peers in a social network might have about the content of a friend.…”
Section: Social Tagging Revamped: Persuasive Techniques and Mutual Momentioning
confidence: 99%
“…In our work, we focus on -and structure the activity within-networks of peers that know each other (i.e., social networks). As friends and family members possess mental models [21] of each other, they are in a privileged position to create rich descriptors of the user-generated multimedia content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• How does group awareness develop over time? For instance, Sangin, Nova, Molinari, and Dillenbourg (2007) have found that the dynamics of group awareness are quite complex, as learners' use of SCANrelevant information is partially dependent on the use of the same information by their collaborators. • What is the relative efficiency of intentional vs. non-intentional metaphors of social navigation?…”
Section: The Future Of Scan Toolsmentioning
confidence: 99%
“…Dillenbourg proposes in [40] a model to represent mutual modelling situations. He uses the notation M(A, B, X) to denote "A knows that B knows X" (equivalent to the epistemic logic notation KAKBX that we present in the next section).…”
Section: Cscl Model Of Mutual Modellingmentioning
confidence: 99%